2018
DOI: 10.1097/qad.0000000000001662
|View full text |Cite
|
Sign up to set email alerts
|

Stool Xpert MTB/RIF and urine lipoarabinomannan for the diagnosis of tuberculosis in hospitalized HIV-infected children

Abstract: Stool Xpert had similar performance compared with sputum/gastric aspirate Xpert to detect TB. Urine LAM had lower sensitivity and specificity, but increased among children with severe immunosuppression. Stool Xpert and urine LAM can aid rapid detection of TB in HIV-infected children using easily accessible samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 34 publications
5
59
1
Order By: Relevance
“…In addition, we compared the accuracy of OS PCR with that of liquid culture of a single induced sputum specimen. We, and others, have previously shown that there is substantial incremental yield from testing additional respiratory specimens 6,14 , and we therefore have likely over-estimated the sensitivity of OS PCR in relation to true disease status. Additional limitations included a small sample size and a focus on a single geographical area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we compared the accuracy of OS PCR with that of liquid culture of a single induced sputum specimen. We, and others, have previously shown that there is substantial incremental yield from testing additional respiratory specimens 6,14 , and we therefore have likely over-estimated the sensitivity of OS PCR in relation to true disease status. Additional limitations included a small sample size and a focus on a single geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to improving TB diagnosis in children is to collect multiple different specimen types with the assumption that the yield would be cumulative. Potentially useful specimen types include gastric aspirates, induced sputum, nasopharyngeal aspirates, stool, urine, and the 'string test' [3][4][5][6] . One of the simplest samples to obtain is a swab of the oral mucosa 7 .…”
mentioning
confidence: 99%
“…The next-generation Xpert MTB/RIF Ultra assay has improved sensitivity (199), but its ability to detect subclinical TB is unknown and still requires a sputum sample for the diagnosis of pulmonary TB. Several non-sputumbased approaches are currently under development for diagnosing active TB in both adults and children, which include M. tuberculosis nucleic acid detection in oral mucosa and stool (200,201) as well the as detection of M. tuberculosis proteins and metabolites in urine (202). The most developed non-sputum-based assay detects urinary lipoarabinomannan (LAM) (203) and is indicated for use in severely immunocompromised HIV-infected hospitalized patients (204).…”
Section: Current Approaches and Incremental Improvements For Subclinimentioning
confidence: 99%
“…Other non-respiratory specimens have been tested using Xpert MTB/RIF in children. Previous studies have shown that stool Xpert has similar performance as gastric aspirate in HIVinfected children (LaCourse et al, 2018) and in those with severe pulmonary disease (Walters et al, 2017), however, processing of stool samples is tedious and may not be readily done in peripheral laboratories.…”
Section: Discussionmentioning
confidence: 99%